Association between serum soluble CD14 and IL‐8 levels and clinical outcome in primary biliary cholangitis. (6th December 2016) - Umemura, Takeji; Sekiguchi, Tomohiro; Joshita, Satoru; Yamazaki, Tomoo; Fujimori, Naoyuki; Shibata, Soichiro; Ichikawa, Yuki; Komatsu, Michiharu; Matsumoto, Akihiro; Shums, Zakera; Norman, Gary L.; Tanaka, Eiji; et al.
Abstract: Background & Aims: Primary biliary cholangitis (PBC) is an autoimmune liver disease characterized by portal inflammation and immune‐mediated destruction of intrahepatic bile ducts that often leads to liver decompensation and liver failure. Although the biochemical response to ursodeoxycholic acid (UDCA) can predict disease outcome in PBC, few biomarkers have been identified as prognostic tools applicable prior to UDCA treatment. We therefore sought to identify such indicators of long‐term outcome in PBC in the Japanese population. Methods: The prebiopsy serum samples and subsequent clinical data of 136 patients with PBC treated with UDCA were analysed over a median follow‐up period of 8.8 years. Serum levels of biomarkers related to microbial translocation (sCD14, EndoCAb and I‐FABP) were measured along with those of 33 cytokines and chemokines and additional auto‐antibodies. Associations between the tested parameters and the clinical outcomes of liver decompensation and liver‐related death/liver transplantation were evaluated using the Cox proportional hazards model with stepwise methods and Kaplan‐Meier analysis. Results: Elevated levels of serum IL‐8, and sCD14 before UDCA therapy were significantly associated with both liver decompensation and liver‐related death/liver transplantation. In multivariate analyses, IL‐8≥46.5 pg/mL or sCD14≥2.0 μg/mL at enrolment demonstrated the same results. Kaplan‐Meier analysis also revealed IL‐8 and sCD14 to be significantly associated with a poor outcome. sCD14 was significantly correlated with IL‐8. EndoCAb and I‐FABP were not related to disease outcome. Conclusions: Serum IL‐8 and sCD14 levels before UDCA therapy represent noninvasive surrogate markers of prognosis in patients with PBC.